ANALISIS UNJUK KERJA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ATAP ON-GRID 11,2 KWP DI RESIDENSIAL BUKIT GADING MEDITERANIA, JAKARTA UTARA - Salsabila Ayu, Laili Asdiyan; Dwi Giriantari, Ida Ayu; Setiawan, I Nyoman (Jurnal SPEKTRUM, 2023)
The implementation of PLTS as the utilization of EBT in Indonesia is still being developed. Government policy through KEN and RUEN targets a national PLTS capacity of 6.5 GW in 2025 and 45 GW in 2050. The PLTS system is implemented from the smallest scale, namely residential, with a new challenge, namely to maintain the performance of the PLTS system in good condition. The object of this research was carried out on an 11.2 kWp on-grid rooftop PV mini-grid system at the Bukit Gading Mediterania Residential. The performance of this rooftop PV system was analyzed using the PVsyst software to determine the potential for electricity production, then calculated the PV system performance parameters such as Yield Factor (Yf) , Yield Reference (Yr), Performance Ratio (PR) and Capacity Utilization Factor (CUF) of PLTS within one year of operation starting June 2021 – May 2022, which is then compared with the results of electricity production and the performance parameters of the PLTS system during operation one year from June 2021 – May 2022. The real production value of the 11.2 kWp on-Grid rooftop PV system for a year is 13,809.6 kWh with performance parameters (Yf Factor), Yield Reference (Yr), Performance Ratio (PR ) and Capacity Utilization Factor (CUF)) respectively are 1233.0 kWh/kWp, 1699.7 kWh/kW, 72.4% and 14.1%. For the PVSyst simulation results, the annual potential of electrical energy from the 11.2 kWp on-grid rooftop PLTS system is 15,649 kWh with performance parameters (Yf), Yield Reference (Yr), Performance Ratio (PR) and Capacity Utilization Factor (Yf). CUF)) respectively were 1,397.23 kWh/kWp, 1,691.3 kWh/kW, 82.6% and 16%.